An aspect-oriented approach to fault-tolerance in grid platforms - Medeiros, Bruno (2011)
Migrating traditional scientific applications to computational Grids requires programming tools that can help programmers to update application behaviour to this kind of platforms. Computational Grids are particularly suited for long running scientific applications, but they are also more prone to faults than desktop machines. The AspectGrid framework aims to develop methodologies and tools that can help to Grid-enable scientific applications, particularly focusing on techniques based on aspect-oriented programming. In this paper we present the aspect-oriented approach taken in the AspectGrid framework to address faults in computational Grids. In the proposed approach, scientific applications are enhanced with fault-tolerance capability by plugging additional modules. The proposed technique is portable across operating systems and minimises the changes required to base applications.